2020
DOI: 10.1002/elan.202060031
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light Photoelectrochemical Sensor for Acetaminophen Determination using a Glassy Carbon Electrode Modified with BiVO4 Nanoparticles

Abstract: A new and simple photoelectrochemical (PEC) sensor using a glassy carbon electrode (GCE) modified with bismuth vanadate (BiVO4) nanoparticles and dihexadecyl phosphate (DHP) film was useful for acetaminophen (AC) determination. In 0.2 mol L−1 phosphate buffer (pH=9), the GCE without modification exhibited the smaller photocurrent (0.86 μA) when compared with GCE modified with 1.0 mg mL−1 or 2.0 mg mL−1 BiVO4 nanoparticles suspension (5.9 and 34 μA, respectively). Based on the photocurrent signal generated thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…TNT_lgPDA composite can be considered as a member of the broad semiconductor–nanocarbon composite family. These materials are capable of photocurrent generation and have decent conductivity and charge transfer kinetics, although not as fast as, e.g., precious metals and alloys. In this context, the spectrum of possible applications of the TNT_lgPDA composite is spanned by several areas such as photoelectrochemical water splitting, removal of pollutants including antibiotics, and photoelectrochemical sensing (PEC) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TNT_lgPDA composite can be considered as a member of the broad semiconductor–nanocarbon composite family. These materials are capable of photocurrent generation and have decent conductivity and charge transfer kinetics, although not as fast as, e.g., precious metals and alloys. In this context, the spectrum of possible applications of the TNT_lgPDA composite is spanned by several areas such as photoelectrochemical water splitting, removal of pollutants including antibiotics, and photoelectrochemical sensing (PEC) .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the detection performance should in principle be better in the PEC experiments compared with the plain electrochemistry. Moreover, the signal-to-noise ratio is also typically smaller because the stimulus signal (light) is different from the collection signal (polarization). , …”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the precise selection of nanomaterials is the basis for the development of highly selective and sensitive supramolecular equipment with affinity to the analyte of interest [101][102][103][104][105][106][107][108][109][110][111][112][113][114]. Recent biological and chemical sensing electrodes have benefited from core/shell nanoparticles [115][116][117][118], metal nanostructures [119][120][121][122][123][124][125][126], oxides [127][128][129][130][131][132][133][134][135], bimetallic compounds [136,137], carbon-based structures [138][139][140] and other mediators [141,142]. Chemical modification is possible for all electrodes used in electrochemical measurements, including carbon paste electrode gold electrodes, screen-printed electrodes and glassy carbon electrodes [143][144]…”
Section: Introductionmentioning
confidence: 99%
“…Therein, transition metal oxide BiVO 4 , with an excellent charge transport property (hole diffusion length L p = 70 nm) [ 14 , 15 ], has emerged as a highly promising electrocatalytic material with good chemical stability, environmental inertness, and low cost [ 16 , 17 ]. Medeiros et al reported that BiVO 4 nanoparticles could be used as a highly efficient and sensitive photoelectrochemical sensor for paracetamol detection [ 18 ]. Generally speaking, morphology optimization can further enhance the electrocatalytic performance of material oxides.…”
Section: Introductionmentioning
confidence: 99%